2009
DOI: 10.1093/humrep/dep442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous testosterone supplementation in gonadotrophin stimulated cycles

Abstract: Despite increased testosterone levels, a short course of androgens had no significant effect on the number of follicles over 10 mm during stimulation with FSH in women of late reproductive age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
2
20
0
3
Order By: Relevance
“…Yet the positive effects of increasing androgen availability in the ovary, in particular, in women displaying a reduced number of growing follicles and/or follicle responsiveness to FSH still have to be clearly demonstrated in properly designed investigations. It is possible that the lukewarm results of studies aiming to examine the effects of exogenous (34)(35)(36)(37)(38)(39)(40) or endogenous (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) androgens are, at least in part, due to methodological limitations, such as dose and duration of treatment. The ''androgen hypothesis'' remains interesting and plausible and should be examined in further prospective and randomized clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the positive effects of increasing androgen availability in the ovary, in particular, in women displaying a reduced number of growing follicles and/or follicle responsiveness to FSH still have to be clearly demonstrated in properly designed investigations. It is possible that the lukewarm results of studies aiming to examine the effects of exogenous (34)(35)(36)(37)(38)(39)(40) or endogenous (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) androgens are, at least in part, due to methodological limitations, such as dose and duration of treatment. The ''androgen hypothesis'' remains interesting and plausible and should be examined in further prospective and randomized clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Massin et al (39), in a placebo-controlled study, failed to show any improvement in ovarian response to COH in 24 poor responders having received T gel (15 mg/d) during the 15 days before the start of FSH treatment. The lack of effectiveness of T pretreatment observed by Massin et al (39) was later confirmed by another study that used 2.5-mg T patches during 12 days before FSH administration (40). The inconclusive results regarding the effectiveness of T pretreatment to improving ovarian response to COH may at least in part be due to problems linked to the intraovarian bioavailability of such a steroid administered systemically at nonvirilizing doses.…”
Section: Systemic Androgen Administrationmentioning
confidence: 94%
See 1 more Smart Citation
“…In a very small group of normal women averaging 42 years of age with a mean AFC of over 12, luteal administration of a T patch for 12 days failed to affect the response to a small dose of FSH (75 IU) (42). Cai et al (15) have shown that only poor responders to a stronger gonadotropin stimulus have reduced GC FSH receptor activity, and (as noted earlier) poor responders have a marked decrease of follicular fluid IGF-I (37).…”
Section: Growth Hormone/igf-i and Ovarian Responsementioning
confidence: 89%
“…hCG could have resulted in an androgen linked priming effect on the follicular recruitment. Pretreatment with testosterone may improve the oocyte retrieval rate [8], but results in randomized controlled studies are not conclusive yet [9].…”
Section: Discussionmentioning
confidence: 99%